Comparison of oxidation efficiency of disperse dyes by chemical and photoelectrocatalytic chlorination and removal of mutagenic activity - Osugi, Marly E. [UNESP]; Rajeshwar, Krishnan; Ferraz, Elisa R. A.; de Oliveira, Danielle P.; Araújo, Angela Regina [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Degradation of Disperse Orange 1, Disperse Red 1 and Disperse Red 13 dyes has been performed using electrochemical oxidation on Pt electrode, chemical chlorination and photoelectrochemical oxidation on Ti/TiO(2) thin film electrodes in NaCl or Na(2)SO(4) medium. 100% discoloration was obtained for all tested methods after 1 h of treatment. Faster color removal was obtained by photoelectrocatalytic oxidation in 0.1 mol L(-1) NaCl pH 4.0 under UV light and an applied potential of +1.0V (vs SCE reference electrode), which indicates also values around 60% of TOC removal. The conventional chlorination method and electrochemical oxidation on Pt electrode resulted in negligible reduction of TOC removal. All dyes showed positive mutagenic activity in the Salmonella/microsome assay with the strain TA98 in the absence and presence of S9 (exogenous metabolic activation). Nevertheless, there is complete reduction of the mutagenic activity after 1 h of photoelectrocatalytic oxidation, suggesting that this process would be good option to remove disperse azo dyes from aqueous media. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Active chlorine; Disperse azo dye; Photoelectrocatalytic oxidation; Mutagenic activity; Ti/TiO(2) electrodes